In regards to Legislative Decree No. 1236 - New Immigration Law - Hixson Araujo-Alvarez, Frank (2016)
On the basis of the new Migration Law, the present article analyzes which were the main problems in the application of previous regulation, taking in count the legal and migratory situation of foreigners that move to Peru, such as the political and regulatory deficiencies in this field. After this, the article analyzes the new law, its contribution, its deficiencies, and the changes that were being implementing already.